Perancangan User Experience Aplikasi Monitoring dan Konseling Pertanian dengan menggunakan Metode Human-Centered Design (Studi Kasus Kabupaten Magetan) - Eko Nur Adi Prasetyo; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
As an agricultural country, Indonesia should prioritize developments in the agricultural sector. Monitoring and counseling have a great effect on increasing the productivity and welfare of farmers. The aim is to monitor the activities carried out by farmers and provide education so that farmers' production techniques develop. The process of agricultural counseling activities still takes a long time. This is because counseling is hampered by distance and materials received by farmers. This was exacerbated during the COVID-19 pandemic because monitoring and counseling activities were constrained by the government's policy of limiting activities. The goal of this research to design a user experience for agricultural monitoring and counseling applications so that the monitoring and counseling process between farmers and extension workers can be done anytime and anywhere. The method used is human-centered design which consists of user context analysis, user needs analysis, solution design and solution design evaluation. the evaluation process uses usability testing and system usability scale. The test was carried out on 5 farmer respondents and 5 extension respondents. testing from the extension workers resulted in an effectiveness value of 82%, an efficiency value of 0.051 goals/sec and a satisfaction value of 80 with grade B. While testing from farmers resulted in an effectiveness value of 87%, an efficiency value of 0.108 goals/sec and a satisfaction value of 80, 5 with grade A.